Concomitant Multiple Revascularizations in Supra-Aortic Arteries: Short-Term Results in 50 Patients - Pyun, H.W.; Suh, D.C.; Kim, J.K.; Kim, J.S.; Choi, Y.J.; Kim, M.-H.; Yang, H.R.; Jang, Y.M.; Ko, M.-S.; Cha, E.Y.; Yang, D.H.; Kim, S.J. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The outcome for simultaneous revascularization of more than 1 supra-aortic arterial stenosis has not been evaluated because of concerns regarding the increased risk of additional procedures. We evaluated the feasibility and safety of concomitant multiple supra-aortic arterial revascularizations (CMSAR).MATERIALS AND METHODS: We retrospectively evaluated 50 consecutive patients who underwent CMSARs with angioplasty and stent placement. The study included a separate lesion group (LG) (n = 28), ipsilateral LG (n = 17) including adjacent (n = 6) and remote (n = 11) tandem lesions, and triple LG (n = 5). We assessed the procedural success (defined as residual stenosis <30%) and periprocedural event rate (ER) (minor or major stroke, and death). We compared the ERs in the lesion (ipsilateral vs separate) and symptom (unstable vs stable) pattern groups with the Fisher exact test.RESULTS: Procedural success was achieved in all patients (50/50). Periprocedural events within 30 days were noted in 5 (10%). ER within 2 days after the procedure was higher in the ipsilateral LG (4/17) than in the separate LG (0/28) (P = .016). Major events consisting of a major stroke and a death occurred in 2 patients in the unstable group (4%) and was more common in the unstable (2 of 7) than in the stable group (0/38) (P = .029). During the mean 11-month follow-up period, there was 1 symptomatic recurrence.CONCLUSION: CMSARs are feasible with a high procedural success rate resulting in a favorable short-term outcome. However, they must be carefully performed in ipsilateral LG, especially in patients in the unstable group.